DNA origami based Au–Ag-core–shell nanoparticle dimers with single-molecule SERS sensitivity. Issue 10 (19th February 2016) - Prinz, J.; Heck, C.; Ellerik, L.; Merk, V.; Bald, I.
Abstract : DNA origami nanostructures are used to arrange gold nanoparticles into dimers with defined distance, which can be exploited as novel substrates for surface enhanced Raman scattering (SERS). Single dye molecules (TAMRA and Cy3) can be placed into the SERS hot spots, with Raman enhancement up to 10 10, which is sufficient to detect single molecules by Raman scattering. Abstract : DNA origami nanostructures are a versatile tool to arrange metal nanostructures and other chemical entities with nanometer precision. In this way gold nanoparticle dimers with defined distance can be constructed, which can be exploited as novel substrates for surface enhanced Raman scattering (SERS). We have optimized the size, composition and arrangement of Au/Ag nanoparticles to create intense SERS hot spots, with Raman enhancement up to 10 10, which is sufficient to detect single molecules by Raman scattering. This is demonstrated using single dye molecules (TAMRA and Cy3) placed into the center of the nanoparticle dimers. In conjunction with the DNA origami nanostructures novel SERS substrates are created, which can in the future be applied to the SERS analysis of more complex biomolecular targets, whose position and conformation within the SERS hot spot can be precisely controlled.